ESTABLISHING PERFORMANCE INDICATORS FOR ACADEMIC ENGLISH PROFICIENCY: A CASE FOR EFL UNIVERSITY STUDENTS - Nakhornsri, Supalak (PUPIL: International Journal of Teaching, Education and Learning, 2020)
In Thailand, the B1 level of the CEFR was specified as the goal of English proficiency for high school or vocational certificate graduates. Therefore, for university levels, students’ English ability equal to the B1 level or above is expected. English proficiency tests are needed to fulfill this assessment purpose. Moreover, one of the considering points is that the test results are generally reported quantitatively without meaningful interpretations. This study attempts to investigate the Target Language Use (TLU) domain of academic English proficiency for EFL university students so that performance indicators can be established. The quality of this developed test was evaluated and the concurrent validity was examined to demonstrate how well the developed test correlated with a well-established test. The sample of the study included 39 informants that provided information about the TLU domain and 30 test takers for the main study. The instruments consisted of a questionnaire asking about the TLU domain and the developed academic English proficiency test. The arithmetic mean and Standard Deviation (S.D.) were employed for the analysis of the TLU domain. Construct validity, reliability, and item analysis were analyzed for test quality. Finally, Pearson’s product-moment was implemented in order to examine concurrent validity. Besides, regression analysis was used to demonstrate if the obtained scores could predict the scores from the standardized test. The findings are significant in several ways. First, these findings are able to provide a clearer concept of the performance indicators of academic English proficiency. The developed test can be a useful instrument for several purposes, for example for placement or achievement. Finally, the assessment of concurrent validity can be useful in terms of test score interpretations.